A Critical Assessment of the Added Value of Territorial Cohesion - Frank Othengrafen; Andreas P. Cornett (European Journal of Spatial Development, 2013)
This paper, by drawing on various interpretations or storylines of territorial cohesion and by referring to the national policy contexts in Denmark and Germany, critically assesses the concept of territorial cohesion and its added value by exploring what difference the formal recognition of territorial cohesion makes for EU, national and regional policymaking in terms of adapted policy objectives, altered perceptions of territory and place and modified policy instruments. It is argued herein that even though territorial cohesion obviously changes the rationales underlying the cohesion policies and strategic European spatial development policies by emphasising the potential of territorial capital for innovation and employment, the concept of territorial capital is not completely new. Some of the objectives or meanings can be found in former EU cohesion or spatial development policies; additionally, some EU member states such as Denmark have pursued this type of strategy since the early 1990s. Additionally, in Germany, instruments for social and economic cohesion already cover territorial aspects, meaning that the added value of the concept of territorial cohesion can critically be questioned. Furthermore, Denmark and Germany are both sceptical with regard to the introduction of new funding priorities and instruments; the old ones obviously work sufficiently as convergence among regions could be achieved from a country-by-country perspective. Nevertheless, an important advantage of the concept of territorial cohesion is that it offers added value for rethinking current (spatial) policies, strategies and instruments in EU member states that do not have such a long tradition or established system of spatial development policies. From this perspective, the concept of territorial cohesion has sharpened the attention paid to the territorial implications of European policies from a broader perspective, and thus it may serve as a conceptual tool to deal with these issues, not only from an economic but also from a spatial planning and policy coordination perspective